Biomechanical Comparison of Three Suspensory Techniques for all Soft Tissue Central Quadriceps Tendon Graft Fixation - Michelle E. Arakgi, M.Sc., M.D., F.R.C.S.C; Timothy A. Burkhart, Ph.D; Takashi Hoshino, M.D; Ryan Degen, M.D; Alan Getgood, M.Phil., M.D., F.R.C.S. (Tr.&Orth.) (Elsevier, 2022)
Purpose: The purpose of this study was to evaluate three different methods of attachment of continuous loop suspensory cortical preparation of all soft tissue central quad tendon grafts compared to a bone block control for anterior cruciate ligament reconstruction on construct displacement and load to failure. Methods: Thirty-two cadaveric central quadriceps tendon (CQT) specimens were harvested, using three clinical techniques for graft fixation: cortical button alone (BTB EB), BTB cortical button with rip-stop suture (BTB RS), and continuous loop cortical button (BTB CL). A control group was also included that consisted of a bone block secured within testing clamps (BTB CON). Specimens were preloaded to 150 N. Tendons were then cyclically loaded between 50 N and 250 N for 1,000 cycles at .5 Hz. Displacement was measured at the point of fixation of the CQT after the 150 N preload, 250 N initial load and every 100th cycle. The specimens were loaded to failure after 1,000 cycles. Results: There was a significant increase in displacement from .32 ± .56 mm for the BTB CON to 1.91 ± 1.13 mm for the BTB RS (P = .014) and 3.85 ± 2.32 mm for the BTB CL condition (P = .023). There was no significant increase in displacement for BTB EB (P = .182). Failure occurred for all of the BTB CL and 62.5% of the BTB EB specimens within the first 50 cycles. Twenty-five percent of the BTB CON specimens and 12.5% BTB RS failed at ∼400 and 500 cycles, respectively. Similar failure loads were observed for the BTB CON and the BTB RS (446.4 ± 151.46 N vs 505.74 ± 131.41 N; P = .99) Failure testing was not feasible for the BTB CL and BTB EB preparation methods. Conclusion: In response to cyclic loading, the three all-soft tissue suspensory conditions experienced significantly greater displacement compared to the bone block controls. None of the soft-tissue conditions appeared superior when compared to each other. Clinical Relevance: It remains unknown which method of soft-tissue suspensory provides optimal fixation. As these autografts become more common, it is essential to evaluate which fixation methods provide superior outcomes